2019
DOI: 10.18203/2349-3291.ijcp20194761
|View full text |Cite
|
Sign up to set email alerts
|

A rare and interesting case of Scarabiasis

Abstract: Scarabiasis or Canthariasis or Beetle disease is an ectoparasitic infection of the gastrointestinal tract, in which the beetles temporarily infest the digestive tract and rarely the urinary tract. Dung beetle belongs to Scarabiaediae family.  It is mostly seen in children aged between 2 to 5 years, who play outdoor for prolonged hours without undergarments. It is a temporary infestation in which early stages of development of beetle takes place in the anus and the adult beetle flies, out of the anus while defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The child we report was also from a rural village. In our case, ultrasound scan of abdomen, per rectal and fecal examination were found to be normal as in previous studies [1]. Similar to this case, previous cases have also reported patients having poor appetite and abdominal cramps [1,2,3,5].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The child we report was also from a rural village. In our case, ultrasound scan of abdomen, per rectal and fecal examination were found to be normal as in previous studies [1]. Similar to this case, previous cases have also reported patients having poor appetite and abdominal cramps [1,2,3,5].…”
Section: Discussionsupporting
confidence: 88%
“…Scarabiasis is an ectoparasitic infestation of the gastrointestinal tract by coprophagous beetles. All reported scarabiasis cases to date have identified that infected children invariably belong to a lower socioeconomical background [1]. The child we report was also from a rural village.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…[1][2][3][4] Gastrointestinal canthariasis is a common infestation in the paediatric age group often leading parents to seek medical attention. [5][6][7][8][9][10] The clinical presentation of canthariasis is usually broad and often unspecific posing a diagnostic challenge to the treating physician leading to empirical treatment with anthelmintics. Stored food materials, dry fruits, breakfast cereals, or precooked cereals have long been considered to serve as a microhabitat for both adult and larval stages of beetles, thus providing a suitable environment for the agent (beetle) and host (human) interaction.…”
Section: Introductionmentioning
confidence: 99%